The Unending Cycle of Education Reforms in Ghana - Tonah, S. (Journal of Education Research in Africa 1 (1): 45-52, 2009)
This paper analyzes the education reform policies of various Ghanaian governments since independence in 1957. It establishes that the reasons given by successive governments for introducing an education reform has been very similar. Ghana has had numerous education reforms and reviews of existing education systems. These reforms have largely not been able to deliver upon their promises, leading to recurrent calls for reforming the education system. The paper argues that the reform of education in Ghana should be seen more as a political programme rather than a well-planned and realistic attempt to resolve the challenges facing the education system. It is therefore unlikely the 2007 education reform will be different from previous ones.
Keywords: Education Reform; Education System; Basic Education; Ghana